Cell-free DNA - Minimally invasive marker of hematological malignancies - Kubaczkova, Veronika; Vrabel, David; Sedlarikova, Lenka; Besse, Lenka; Sevcikova, Sabina (European journal of haematology, 2017)
Although tumor cells are the most reliable source of tumor DNA, biopsy of the tumor is an invasive procedure that should be avoided in some cases. The main limitation of any biopsy is sampling of one tumor site, which may not represent all malignant clones due to the heterogeneity of the tumor. These clones respond to treatment differently and thus directly influence survival of the patient. Circulating cell-free DNA (cfDNA) is released from multiple tumor sites, reflects overall heterogeneity of the tumor, and correlates with its progression. Detection of tumor-specific genetic and epigenetic aberrations in cfDNA could have a direct impact on molecular diagnosis, prognosis, follow-up of disease, monitoring of minimal residual disease, and response to treatment. While most cfDNA data are still experimental, they are very promising. This review focuses on cfDNA in hematological malignancies.
Keywords: acute myeloid leukemia; myelodysplastic syndromes; multiple myeloma; lidé; Molecular Diagnostic Techniques; Liquid Biopsy; prognóza; Genetic Variation; cirkulující nádorová DNA; diagnostické techniky molekulární; hematologické nádory; nádorové biomarkery; Hematologic Neoplasms; Circulating Tumor DNA; Prognosis; acute lymphoblastic leukemia; Biomarkers, Tumor; genetická variace; tekutá biopsie; Humans